2003
DOI: 10.4315/0362-028x-66.1.103
|View full text |Cite
|
Sign up to set email alerts
|

A Competitive Polymerase Chain Reaction–Based Approach for the Identification and Semiquantification of Mitochondrial DNA in Differently Heat-Treated Bovine Meat and Bone Meal

Abstract: The risk of bovine spongiform encephalopathy propagation was drastically reduced after the European Union (EU) Health Authorities adopted restrictions involving a ban on animal-derived proteins in the diet of farm animals. Currently, the EU's of cially recommended method for controlling meat and bone meal (MBM) in animal feed is the microscopic method, which involves the identi cation of bone fragments on the basis of their morphological characteristics. Recently, we demonstrated that a polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Species-specific PCR based assays have previously been reported for the identification of animal derived material in feedstuffs by amplifying mtDNA genes as cytochrome b, ATPase 8, ATPase 6 and 12 S rRNA (Chen, Wen, Ding, Kao, & Kuo, 2003;Herman, 2001;Myers et al, 2001;Rodríguez et al, 2004). Nevertheless, primers here reported were designed to obtain amplicons smaller than 120 bp, detectable in highly degraded material (Frezza et al, 2003;Chiappini et al, 2005). Indeed, during feedstuffs preparation, the DNA is degraded due to the hyperbaric treatment applied (133°C/3 bar for 20 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species-specific PCR based assays have previously been reported for the identification of animal derived material in feedstuffs by amplifying mtDNA genes as cytochrome b, ATPase 8, ATPase 6 and 12 S rRNA (Chen, Wen, Ding, Kao, & Kuo, 2003;Herman, 2001;Myers et al, 2001;Rodríguez et al, 2004). Nevertheless, primers here reported were designed to obtain amplicons smaller than 120 bp, detectable in highly degraded material (Frezza et al, 2003;Chiappini et al, 2005). Indeed, during feedstuffs preparation, the DNA is degraded due to the hyperbaric treatment applied (133°C/3 bar for 20 min).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to conventional PCR, RT-PCR has the advantage of quantifying the small size products (from 66 to 145 bp), amplified from highly degraded source material, like rendered MBM. Recently (Frezza et al, 2003), we demonstrated that short amplicons can be used to detect the presence of bovine mitochondrial DNA (mtDNA) in MBM samples treated according to the current European legislation (133°C, 20′, 3 bars) (Dept. of Agr., Food and Rur.…”
Section: Introductionmentioning
confidence: 99%
“…appropriate analytical tool. However, there are few Consequently, most systems for the detection of reports examining the design and optimization of DNA from highly processed matrices used amplireal-time PCR assays, although many studies cite cons of approximately 300 bp (Bottero et al 2003; various significant parameters that must be consid- Frezza et al 2003;Tartaglia et al 1998) and the ered during the design process for efficient amplifineed for gel visualization meant that the amplicons cation and therefore sensitive assays. were usually over 130 bp.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its compact circular shape, mtDNA is relatively stable and thus highly suitable for DNA detection in heat-treated materials. Nevertheless, mtDNA might be damaged/fragmented during the MBM rendering procedure 4), 7) . Recently, a specific detection method for porcine DNA using real-time PCR equipment was reported by Tanabe, et al 11) .…”
Section: Introductionmentioning
confidence: 99%
“…The chosen target sequences for PCR amplification, namely mitochondrial DNA (mtATP8 and mtATP6), have relatively high degrees of variation among vertebrates 7) . Similar sequences are not found in plants 8) .…”
Section: Introductionmentioning
confidence: 99%